2021
DOI: 10.1097/md.0000000000026564
|View full text |Cite
|
Sign up to set email alerts
|

Longer length of post-acute care stay causes greater functional improvements in poststroke patients

Abstract: Post-acute care (PAC) is a type of transitional care for poststroke patients after the acute medical stage; it offers a relatively intensive rehabilitative program. Under Taiwan's National Health Insurance guidelines, the only patients who can transfer to PAC institutions are those who have had an acute stroke in the previous month, are in a relatively stable medical condition, and have the potential for improvement after aggressive rehabilitation. Poststroke patients receive physical, occupational, and speech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…However, it should be noted that the greater the PAC LOS, the greater the number of improved rehabilitation assessments. The situation is similar to a previous study in Taiwan showing post-stroke patients having longer stay in a PAC institution have superior ADL function, balance and coordination, walking speed, and upper-limb dexterity and sensory function (Tung et al, 2021). Despite an upper limit in the PAC payment for LOS, it was suggested that the disability status of patients should be taken into account in planning PAC with preset rehabilitation goals (Tan et al, 2009(Tan et al, , 2010.…”
Section: Discussionsupporting
confidence: 79%
“…However, it should be noted that the greater the PAC LOS, the greater the number of improved rehabilitation assessments. The situation is similar to a previous study in Taiwan showing post-stroke patients having longer stay in a PAC institution have superior ADL function, balance and coordination, walking speed, and upper-limb dexterity and sensory function (Tung et al, 2021). Despite an upper limit in the PAC payment for LOS, it was suggested that the disability status of patients should be taken into account in planning PAC with preset rehabilitation goals (Tan et al, 2009(Tan et al, , 2010.…”
Section: Discussionsupporting
confidence: 79%
“…In 2017, Lai et al reported that 76.8% of stroke patients returned to their homes and communities following the completion of the PAC program in Taiwan 10 . Several factors are associated with the outcomes of patients utilizing the post-stroke PAC program, including the duration of PAC stay 11 and stroke type 12 . However, most hospitals authorized to provide the PAC program in Taiwan also have non-PAC services.…”
Section: Discussionmentioning
confidence: 99%
“…Organizing patient transfers through negotiations with other hospitals is reportedly a reason for longer stays in the emergency department [ 41 ]: such transfers are unnecessary in the case of home discharge. Providing home-visit services to complement home discharge would help patients or caregivers achieve earlier discharge [ 42 ]; that would avoid some of the disadvantages caused by shorter hospital stays [ 43 ].…”
Section: Discussionmentioning
confidence: 99%